2019
DOI: 10.1186/s12870-019-1644-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CO2 concentration promotes photosynthesis of grape (Vitis vinifera L. cv. ‘Pinot noir’) plantlet in vitro by regulating RbcS and Rca revealed by proteomic and transcriptomic profiles

Abstract: BackgroundPlant photosynthesis can be improved by elevated CO2 concentration (eCO2). In vitro growth under CO2 enriched environment can lead to greater biomass accumulation than the conventional in micropropagation. However, little is know about how eCO2 promotes transformation of grape plantlets in vitro from heterotrophic to autotrophic. In addition, how photosynthesis-related genes and their proteins are expressed under eCO2 and the mechanisms of how eCO2 regulates RbcS, Rca and their proteins have not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 66 publications
0
12
0
1
Order By: Relevance
“…Indeed, the impact of an increase in atmospheric CO 2 concentration on plant carbon metabolism, notably on photosynthesis and respiration processes, has been previously reported (Dusenge et al, 2019). Zhao et al (2019) also demonstrated that photosynthesis of in vitro grape plantlet was promoted by elevated CO 2 concentration. These modifications may directly affect primary and secondary plant metabolism, thus leading to substantial changes in fruit composition.…”
Section: Introductionmentioning
confidence: 80%
“…Indeed, the impact of an increase in atmospheric CO 2 concentration on plant carbon metabolism, notably on photosynthesis and respiration processes, has been previously reported (Dusenge et al, 2019). Zhao et al (2019) also demonstrated that photosynthesis of in vitro grape plantlet was promoted by elevated CO 2 concentration. These modifications may directly affect primary and secondary plant metabolism, thus leading to substantial changes in fruit composition.…”
Section: Introductionmentioning
confidence: 80%
“…In grape (Vitis vinifera L. cv. 'Pinot Noir'), Zhao et al [17] conducted transcriptome profiling and found that the ribulose bisphosphate carboxylase small chain (RbcS) and rubisco activase (Rca) genes are up-regulated upon increased CO 2 concentration, which promotes photosynthesis and accelerates transition of grape plantlets from heterotrophic to autotrophic.…”
Section: Introductionmentioning
confidence: 99%
“…Our integrated model overcomes this and not only suggests the changes in mRNA levels and how these affect photosynthetic metabolism, but was able to predict the acclimation of photosynthetic CO 2 assimilation that had been observed (Figure 1). Previous studies have reported proteome-level changes in response to elevated CO 2 in soybean and other crop species (Ainsworth and Long, 2005, Bokhari et al, 2007, Taub et al, 2007, Yousuf et al, 2017, Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The altered photosynthetic phenotype likely resulted from adjusted enzyme concentrations in soybean leaves grown under ambient and elevated CO 2 concentrations. Such CO 2 -induced changes in protein concentrations was shown for total protein concentration in barley, rice, wheat, soybean, and potato (Taub et al, 2007) and for specific proteins via proteomic analysis in rice (Bokhari et al, 2007), wheat (Yousuf et al, 2017), and grape (Zhao et al, 2019). A decrease in the quantity of Rubisco is a pervading feature of plants grown in the field under elevated [CO 2 ] (Ainsworth and Long, 2005).…”
Section: Multiscale Model Developmentmentioning
confidence: 96%